Evaluation of the Ultrasonic Flaw Detector Inspection on Single Vee Butt Welded of Carbon Steel Plate Using Three Different Couplant - Baduhalin, Muhammad Adam; Abdul Rani, Abdul Syahmie Azree; M.Yusup, Eliza (Journal of Advanced Mechanical Engineering Applications, 2023)
Carbon steel plate with single vee butt welded was inspected with an ultrasonic flaw detector (UTFD) using an angle probe. Various types of couplants have been used to study their effects on ultrasonic transmission. The acoustic impedance of the couplant affects the transmission of ultrasonic waves. As a result, welding flaws were found on the root and central area of the butt weld plate. The results also show that honey has the smallest percentage difference (234.42) in terms of size accuracy compared to water (362.89) and baby oil (370.04) in identifying and measuring defect size. However, there are other factors to be considered when performing an UTFD testing. In summary, UTFD is the only method of NDT that can detect and measure all subsurface defects in the weld area, and honey gave the best results for the couplant used.